FACTORS INFLUENCING SELF-CARE AMONG PATIENTS WITH HEART FAILURE IN INDONESIA - Astuti, Rika Puji; Nurdina, Gina; Herdiman, Herdiman (Himpunan Perawat Medikal Bedah Indonesia (HIPMEBI) Regional Jawa Barat, 2025)
Effective self-care is essential for individuals with heart failure to maintain physical stability, prevent symptom progression, and detect early signs of clinical deterioration. Despite its importance, many patients experience difficulties in adhering to self-care behaviors. Previous studies have indicated that various factors—including educational background, depressive symptoms, digital health literacy, knowledge of heart failure, and social support—may influence self-care capacity. This study aims to examine the factors that contribute to self-care behaviors among heart failure patients. A quantitative approach was applied using a cross-sectional design. A total of 119 participants were recruited from a cardiac outpatient clinic using convenience sampling. Data collection instruments included demographic questionnaires, the Self-Care of Heart Failure Index (SCHFI), Patient Health Questionnaire-9 (PHQ-9), eHealth Literacy Scale (eHEALS), Dutch Heart Failure Knowledge Scale (DHFKS), and the Medical Outcomes Study Social Support Survey (MOS-SSS). Pearson’s correlation was used for bivariate analysis, and linear regression was conducted for multivariate analysis. The findings indicated a significant relationship between depressive symptoms and self-care (p = 0.004, r = 0.259), and between eHealth literacy and self-care (p = 0.003, r = 0.267). No significant associations were observed between self-care and education level (p = 0.062), knowledge level (p = 0.399), or social support (p = 0.644). In summary, depressive symptoms and eHealth literacy were found to be significant predictors of self-care in individuals with heart failure. Among these, eHealth literacy had the greatest impact, highlighting the importance of digital competency in managing chronic conditions.